Remarkable features of ovarian morphology and reproductive hormones in insulin-resistant Zucker fatty (fa/fa) rats - Manase Kengo; Kitajima Yoshimitsu; Henmi Hirofumi; Fujimoto Takashi; Baba Tsuyoshi; Nagasawa Kunihiko; Shimizu Ayumi; Kiya Tamotsu; Endo Toshiaki; Honnma Hiroyuki; Ishioka Shinichi; Ito Eiki; et al. (BMC, 2010)
Abstract Background Zucker fatty (fa/fa) rats are a well-understood model of obesity and hyperinsulinemia. It is now thought that obesity/hyperinsulinemia is an important cause of endocrinological abnormality, but to date there have been no reports on the changes in ovarian morphology or the ovarian androgen profile in rat models of obesity and insulin resistance. Methods In this study we investigated the effects of obesity and hyperinsulinemia on ovarian morphology and the hormone profile in insulin-resistant Zucker fatty rats (5, 8, 12 and 16 weeks of age, n = 6-7). Results Ovaries from 5-week-old fatty rats had significantly greater total and atretic follicle numbers, and higher atretic-to-total follicle ratios than those from lean rats. Ovaries from 12- and 16-week-old fatty rats showed interstitial cell hyperplasia and numerous cysts with features of advanced follicular atresia. In addition, serum testosterone and androstenedione levels significantly declined in fatty rats from age 8 to 16 weeks, so that fatty rats showed significantly lower levels of serum testosterone (12 and 16 weeks) and androstenedione (all weeks) than lean rats. This may reflect a reduction of androgen synthesis during follicular atresia. Serum adiponectin levels were high in immature fatty rats, and although the levels declined significantly as they matured, it remained significantly higher in fatty rats than in lean rats. On the other hand, levels of ovarian adiponectin and its receptors were significantly lower in mature fatty rats than in lean mature rats or immature fatty rats. Conclusions Our findings indicate that ovarian morphology and hormone profiles are significantly altered by the continuous insulin resistance in Zucker fatty rats. Simultaneously, abrupt reductions in serum and ovarian adiponectin also likely contribute to the infertility seen in fatty rats.